Oxidative Stress in Dog with Heart Failure: The Role of Dietary Fatty Acids and Antioxidants - Emmanuelle Sagols; Nathalie Priymenko (Veterinary Medicine International)
In dogs with heart failure, cell oxygenation and cellular metabolism do not work properly, leading to the production of a large amount of free radicals. In the organism, these free radicals are responsible of major cellular damages: this is oxidative stress. However, a suitable food intake plays an important role in limiting this phenomenon: on the one hand, the presence of essential fatty acids in the composition of membranes decreases sensitivity of cells to free radicals and constitutes a first protection against the oxidative stress; on the other hand, coenzyme Q10, vitamin E, and polyphenols are antioxidant molecules which can help cells to neutralize these free radicals.